Where is Wilderness in Brazil? The Concept of Primitive Natural Areas for Brazilian Protected Areas - Burlamaqui Bradford, Renata (2022)
This article presents the concept of primitive natural areas (ANPs) as a way to expand the diversity of recreational opportunities in Brazilian protected areas. ANPs have a primitive character, with a high level of naturalness and minimal or nonexistent contemporary human intervention, not even established trails or signs. These areas offer recreational and social opportunities with a high level of adventure, risk, and solitude, demanding self-sufficiency from visitors. The article presents the foundations for the concept, including the characteristics of wilderness areas, widespread in the United States, and the guidelines for category 1b of the International Union for Conservation of Nature. It also presents the relationship between ANP and the Brazilian zoning scheme and the class of recreation experiences of the "Rol de Oportunidades de Visitação em Unidades de Conservação." Finally, considerations about the Brazilian planning instruments, the diversity of recreational opportunities and the ANPs are presented.Â